Altman model for measuring financial distress: Comparative analysis between sharia and conventional insurance companies - Nustini, Yuni; Amiruddin, Ahmad Rijal (Journal of Contemporary Accounting, 2019)
The purpose of this study is to examine the financial ratios that affect the condition of financial distress of an insurance company employing the Altman model and then comparing the financial distress of Islamic and conventional insurance companies. The sample of this study consisted of 36 Islamic insurance companies and 49 conventional, the sample was selected by purposive sampling. The statistical method used to test the research hypothesis is multiple linear regression analysis and sample t-test. The results showed that Retained Earning to Total Asset (RETA), Earning Before Interest and Taxes to Total Asset (EBITTA), Book Value of Equity to Book Value of Total Debt (BVEBVTD) are significant variables to determine the financial company's distress and there are differences between the financial distress of Islamic financial distress insurance and conventional insurance. The results of this study are expected to provide information for internal and external parties about the Altman ratio which is very dominant in predicting financial distress as well as providing information on which insurance company is good for avoiding financial distress. For parties with an interest in the differences between Islamic insurance companies and conventional insurance, the results of this study can be used as material for consideration and evaluation of determining which company to choose.